Critical Review of «The Innovation Delusion»: How Our Obsession with the New Has Disrupted the Work That Matters Most (Vinsel & Russell, 2020) - Brandão, Tiago (NOvation — Critical Studies of Innovation, 2025)
The Innovation Delusion: How Our Obsession with the New Has Disrupted the Work That Matters Most (2020), by Lee Vinsel and Andrew L. Russell, presents a blistering critique of the contemporary ideology of innovation, exposing what the authors call «innovation-speak» – a hegemonic discourse that glorifies disruptive change and marginalises the essential work of maintenance. The Innovation Delusion, by Lee Vinsel and Andrew L. Russell, published not many years ago (2020), is among the scholar books one must read, especially for younger generations and policymakers around the world. Many years ago, Steven Shapin (1989) unearthed the role of the technician in modern science. Innovation Delusion does the same for hidden activities in innovation — i.e., activities related to technology and engineering. Maintenance, upkeep and care is the motto behind Vinsel and Russell’s book.